Quantitative analysis of smart contracts (fairness) - Tan, Jeremiah Shi Jie (Nanyang Technological University, 2022)
A smart contract is a program that runs on the Ethereum blockchain. Users can define rules and the smart contract automatically enforces these rules and sends transactions over the network. Smart contracts are autonomous, fast and accurate. Smarts contracts have a variety of use cases, such as financial services, auctions and non-fungible tokens (NFTs). In this report, we will be focusing on voting smart contracts. There are many different voting methods among voting smart contracts and they can give different results despite the same voter’s preferences. As a result, we will study some voting methods and fairness criteria to evaluate the fairness of voting smart contracts